ONLINE PUBLICATIONS INFORMATION WAR THE TOPIC IN LIGHTING GENRES AND MODERN FORMATS IMPORTANCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
A significant share of information warfare content is attributed to all known, online publications operating on the Internet. The breadth of its capabilities compared to traditional media is precisely what makes it useful in covering information warfare processes, as evidenced by the information environment in today's globalization process. This article studies the role of genres and new formats widely used in Internet publications in covering information warfare.